Thermal inactivation of Phytophthora nicotianae - Coelho, L. [UNESP]; Mitchell, D. J. [UNESP]; Chellemi, D. O. [UNESP] (Scientific Societies, 2000)
Phytophthora nicotianae was added to pasteurized soil at the rate of 500 laboratory-produced chlamydospores per gram of soil and exposed to temperatures ranging from 35 to 53°C for 20 days. The time required to reduce soil populations to residual levels (0.2 propagule per gram of soil or less) decreased with increasing temperatures. Addition of cabbage residue to the soil reduced the time required to inactivate chlamydo spores. Temperature regimes were established to simulate daily temperature changes observed in the field, with a high temperature of 47°C for 3 h/day, and were good estimators of the efficacy of soil solarization for the control of P. nicotianae in soil. Cabbage amendment reduced the time required to inactivate chlamydospores of P. nicotianae and its effect was more pronounced at lower temperature regimes.
Keywords: Brassica oleracea; Intermittent heat; Nonchemical control; Organic amendment; cabbage; cell inactivation; chlamydospore; fungal spore; fungus cell; soil inoculation; temperature; Phytophthora nicotianae